Optimal design research structure rollover safety universe coach follow standards European safety ECE R66 - Pham, Hong Thao; Le, Van Thoai; Le, Cao Hieu; Phi, Van Cuong; Le, Van Cuong (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Computer applications modeling finite element universe bus seats are technical topics. Then, skeletal model starting stiffness was analyzed using simulation to meet the European tilt safety requirement ECE R66. As a result, the skeleton’s initial volume and hardness are higher. Reduce the volume of the passenger car frame by performing a thickness reduction in the conventional manner until skeletal deformation reaches a safe space. continuing to improve by altering the structural skeleton’s design at deformationaffecting positions. Results showed improved volumes decreased by 5%. However, this improved method is not really optimal. Conduct simulation experimental design using optimization problems with an empirical regression equation from SPSS. applying Matlab GA’s genetic algorithms to the empirical regression equation. Results achieved as the total volume of the selected variables decreased 18.5% compared to the prior optimization.